Controllable Synthesis of Carbon Dots with Excitation‐Wavelength‐Dependent or Independent Photoluminescence for the Selective and Sensitive Detection of Co2+ Ions. Issue 42 (12th November 2018) - Wang, Lanhui; Lin, Kui; Trinchi, Adrian; Cole, Ivan S.; Tian, Fei
Abstract: Fluorescent carbon dots (CDs) with excitation‐wavelength‐dependent and excitation‐wavelength‐independent emission have been prepared with varying amounts citric acid (CA), ethylenediamin end‐capped polyethylenimine (PEI‐EC) and sodium borohydride (NaBH4 ), their structure, optical and chemical sensing properties have been also systematically investigated. The varying of NaBH4 and PEI‐EC renders the structure and surface state change as well as photoluminescence (PL) properties. The results indicated that NaBH4 made the CDs sensitive to Co 2+ ions, whilst the PEI‐EC served to increase their sensitivity. The synergistic roles that both NaBH4 and PEI‐EC played on the selective and sensitive detection of Co 2+ were achieved via a simple adjustment of the mass ratios during synthesis. Furthermore, the PL intensity was gradually recovered until completely restored with the addition of chelating agent ethylenediaminetetraacetic acid (EDTA) to the Co 2+ quenched CDs solutions. This work provided quantitatively preparation and controllable synthesis of excitation‐wavelength‐dependent or independent CDs for the development of PL based sensors. Abstract : Fluorescent carbon dots (CDs) with excitation‐wavelength‐dependent or independent emission has been synthesized through a simple approach. The CDs have sensing selectivity for Co 2 in the nano‐molar range, and the degree of sensitivity correlates with the density of amides formed on the surface of CDs. The sensing mechanism of CDs is attributed to the weak interaction between amides and Co 2+ .